Monsoonal Influence and Variability of Water Quality, Phytoplankton Biomass in the Tropical Coastal Waters – A Multivariate Statistical Approach - Naik, Subrat; Mishra, Rajani Kanta; Sahu, K. C.; Lotliker, Aneesh A.; Panda, U. S.; Mishra, Pravakar (Frontiers in Marine Science, 2020)
Rushikulya estuary is rich in biodiversity facing significant changes in recent periods due to pollution/anthropogenic impacts from the industries and growing urbanization along the banks of the river. This estuary caters mass nesting of Olive Ridley sea turtles and one of the world's largest rookery in India. In view of the above the present study examined, the seasonal variability of water quality parameters (water temperature, pH, salinity, dissolved oxygen, total suspended matter, inorganic nutrients (NO2-N, NO3-N, NH4-N, PO4-P and SiO4-Si) and the phytopigment i.e. Chlorophyll-a (chl-a) from the seawater samples of three different seasons pre-monsoon, monsoon and post-monsoon.Time-series observations were made at five locations off Rushikulya estuary, Bay of Bengal from March 2011 to February 2013. A wide range of nutrient concentrations except for NO2-N varied from 0.89 - 3.62 µmol/l in the NO3-N, from 1.36 - 6.81 µmol/l in the NH4-N, from 0.66 - 3.45 µmol/l in the PO4- P and from 0.89 -7.97 µmol/l in the SiO4-Si. The highest chl-a (3.72 mg/m3) was recorded during pre-monsoon than monsoon and post monsoon. Factor analysis (FA), showed that three underlying factors, each during pre-monsoon, monsoon and post-monsoon influencing the water quality to the extent of 75.02 %, 67.33 % and 66.37 % respectively. The significant result from a statistical view of non-metric multidimensional scaling (nm-MDS) and cluster analysis (CA) revealed that the chl-a variability was due to the direct influence of nutrients than the physical parameters.Correlation analysis revealed that chl-a was positive correlation with DO, NO2, NO3, PO4 and SiO4, while negative with salinity in pre-monsoon and monsoon. The composite results indicated that the study area is well oxygenated, rich in nutrients and chl-a distribution represents typical upper ocean dynamics and food chain linked to the pristine coastal and ecologically rich ecosystem.